KEPADATAN JENTIK Aedes aegypti SEBAGAI VEKTOR DEMAM BERDARAH DENGUE (DBD) DI DESA KALIANCAR WONOGIRI - Leona Dwiyan Marahema; Rinda Binugraheni (Klinikal Sains : Jurnal Analis Kesehatan, 2021)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus which is transmitted through the bite of the Aedes sp. These mosquitoes are found throughout the world and their breeding is quite fast. Density of larvae found in breeding sites in an area. This density can be measured by entomological indicators. This larval density measurement can indicate the potential for larvae in Kaliancar Village, Selogiri District, Wonogiri Regency. This research is an observational study (survey) with cross sectional. The sampling technique used is simple random sampling with single larvae method. The samples of this study were 100 houses of residents of Kaliancar Village RW 01, RW 03, RW 04 and RW 05. The results showed that the HI value was 20%, CI 7,22%, BI 20%, ABJ 80% and DF 3,66. The conclusion of this study is that the larval density in Kaliancar Village, Selogiri District, Wonogiri Regency is classified as moderate because the DF value is on a scale of 3 to 4 with an average of 3,66.